MADE BY ORDER DAN PERMINTAAN KONSUMEN:PENDEKATAN MARKETING SYARIAH DI LAMONE COFFE SHOP - Safitri, Nurlisa; Hamjan, Andi Lisa Aryani; Astuti, Widya; Karyono, Otong; S, Arifin (Politeknik Bisnis Indonesia, 2025)
This paper discusses the implementation of the made by order system in increasing consumer demand from the perspective of Islamic marketing (a case study at Lamone Coffee Shop). The main issues examined are the application of the made by order system in boosting demand and customer perceptions of its implementation at Lamone Coffee Shop. This study uses a qualitative field research method with an Islamic economic and marketing approach. Data were collected through direct observation and interviews with the business owner, employees, and customers. The findings indicate that the implementation of the made by order system has a positive effect on increasing consumer demand due to its personalized services tailored to customer preferences. The business owner noted that this system improves operational efficiency, although challenges remain regarding the availability of raw materials which may affect production time. Overall, this system adds value to service quality and aligns with the principles of Islamic marketing, which are based on the exemplary character of Prophet Muhammad (ṣiddiq, amānah, fatānah, tablīgh, and istiqāmah). This paper is expected to contribute to the development of scientific knowledge in general and Islamic studies in particular.